Perceived Social Support in Relation with Age and Gender: A Cross- Sectional Study among Yazidi IDPs in KRI - Mustafa, Rushdi Ali Merza; Hussein, Hozan Salih (Sulaimani Journal for Humanities, 2023)
The troops of so-called Islamic State of Iraq and the Levant (ISIL) brutally attacked the Yazidis who are a Kurdish minority in Iraq and this known as the crime of genocide in August 2014. As a result of this act, they became internally displaced people (IDP) in the camps in Kurdistan Region of Iraq (KRI). The aim of this study is to assess the level of perceived social support and its association with age, and determine gender differences. To this end, a cross-sectional study was conducted among 611 Yazidi IDP adults (males = 304, females = 307) in four camps in Sulaymaniyah and Duhok governorates. Using a convenient sampling technique for gathering the desired data, we conducted descriptive and inferential statistical analyses to know the level of the participants’ perceived social support and their association with age and gender. The results of our statistical analyses indicated a high level of perceived social support among the participants which was 5.25, considered as a high support. Also, regarding the subscales of perceived social support (family, friend and significant others), they reported higher social support from the family subscale. The results of our study did not confirm any relationship between age and perceived social support and there was not gender difference pertaining to perceived social support. The results of our study offer implications to professional stakeholders to provide more psychoeducation and awareness on the importance of social support among Yazidis as they live in the camps.
Keywords: Perceived social support; IDPs; Age; Gender; Yazidi